(untitled) (Research, Society and Development, 2021)
The aim of this article is to characterize the oral clinical implications and the potential contribution of dentistry to the quality of life of people in palliative care. Articles from the last 10 years, related to the subject were searched in the PUBMED and Scielo databases with the keywords: "palliative care", "dental care" and "oral health". Seven articles were selected from the systematized search and with the application of inclusion and exclusion criteria. The main oral manifestations of patients in palliative care are xerostomy, dental caries, candidosis and mucositis, and the presence of the dental surgeon seems to contribute to the maintenance of quality of life at acceptable levels, even though people are dying. It is perceived by the exposed that the approach of the dental surgeon is necessary in the scope of health promotion, prevention of aggravations and recovery of damage rehabilitation, which make possible the maintenance of quality of life and that this attention is still neglected, due to the lack of obligation of the dental surgeon in the lines of care of terminal patients. More studies on the influence of dental care in the maintenance of quality of life in patients under palliative care are necessary to promote and ratify the importance of the dental surgeon in the team of integral health care of this public.